Risk Factors for Postoperative Infections After Single-Level Lumbar Fusion Surgery. Issue 3 (1st February 2018) - Lim, Seokchun; Edelstein, Adam I.; Patel, Alpesh A.; Kim, Bobby D.; Kim, John Y.S.
Abstract : Study Design: Retrospective multivariate analysis of a prospectively collected, multicenter database. Objective: To identify patient characteristics and perioperative risk factors associated with postoperative infectious complications after single-level lumbar fusion (SLLF) surgery. Summary of Background Data: Postoperative infection is a known complication after lumbar fusion. Risk factors for infectious complications after lumbar fusion have not been investigated using select set of SLLF procedures. Methods: Patients who underwent SLLF between 2006 and 2011 were identified from the American College of Surgeons National Surgical Quality Improvement Program database. Multivariate logistic regression analyses were performed to identify pre- and intraoperative risk factors associated with postoperative infection. Results: A total of 3353 patients were analyzed in this study. Overall, 173 (5.2%) patients experienced a postoperative infection, including 86 (2.6%) surgical site infections (SSIs) and 111 (3.3%) non-SSI infectious complications (pneumonia, urinary tract infection, sepsis/septic shock). Twenty-four (0.7%) patients experienced both SSI and non-SSI infectious complications. Postoperative SSI were associated with obesity (odds ratio [OR], 1.628; 95% confidence interval [CI], 1.042–2.544), American Society of Anesthesiologists class more than 2 (OR, 2.078; 95% CI, 1.309–3.299), and operative time more than 6 hours (OR, 2.573; 95% CI, 1.310–5.056). Risk factors for non-SSI infectious complications included age (60–69 yr; OR, 3.279; 95% CI, 1.541–6.980; and ≥70 yr; OR, 3.348; 95% CI, 1.519–7.378), female sex (OR, 1.791; 95% CI, 1.183–2.711), creatinine more than 1.5 mg/dL (OR, 2.400; 95% CI, 1.138–5.062), American Society of Anesthesiologists class more than 2 (OR, 1.835; 95% CI, 1.177–2.860), and operative time more than 6 hours (OR, 3.563; 95% CI, 2.082–6.097). Conclusion: Across a wide study population, we identified that obesity, advanced American Society of Anesthesiologists classification, and longer operative time were predictive of postoperative SSI. We also demonstrated that increased age, female sex, serum creatinine more than 1.5 mg/dL, and prolonged operative duration are associated with non-SSI infectious complications after SLLF. Continued efforts to elucidate and optimize perioperative risk factors are warranted to improve outcomes in patients requiring spinal fusion. Level of Evidence: 3